Factors Affecting Salesperson Performance: The Case of Fast-Moving Consumer Goods - Ni Cening Nicky Prasada Gayatri; Wanda Artabella Kurniawati; Yoga Angka Wijaya; Anita Maharani (Jurnal Manajemen, 2026)
The purpose of this study is to examine the influence of factors suspected of influencing salesperson performance at PT. Rodamas. Literatures discussed include concepts and hypotheses related to salesperson performance. The research approach applied in this study is quantitative, involving one of the largest Fast Moving Consumer Goods (FMCG) companies in Indonesia, PT. Rodamas. Samples were determined using the sampling formula, resulting in 291 respondents that was selected based on Java Island’s. To analyse data according to the research model, we apply regression analysis with a specific technique to explore the effect of moderation. The results obtained indicate that two of the three hypotheses are supported, while one is not. The implication of this research result is that the company needs to follow up on this research result to apply it to policies and implement it in the company to improve salesperson performance.